2014
DOI: 10.1016/j.jpainsymman.2013.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Advance Directives and a Health Care Proxy on Doctors' Decisions: A Randomized Trial

Abstract: Advance directives and proxy opinions are equally effective in influencing doctors' decisions, but having both has the strongest effect. The format of the advance directive and the identity of the proxy have little influence on decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 37 publications
4
17
0
4
Order By: Relevance
“…In support of this interpretation, a small clinical trial recently demonstrated that patients with ESRD who engaged in an advance care planning intervention with their surrogate were twice as likely to discontinue dialysis compared with patients who did not receive the intervention (3). In our study, the separate contributions of surrogates and treatment-limiting directives seemed to be mutually reinforcing in most situations (32). At the same time, the presence of a surrogate was associated with a higher likelihood of receiving care that was discordant with a treatmentlimiting directive.…”
Section: Discussionsupporting
confidence: 75%
“…In support of this interpretation, a small clinical trial recently demonstrated that patients with ESRD who engaged in an advance care planning intervention with their surrogate were twice as likely to discontinue dialysis compared with patients who did not receive the intervention (3). In our study, the separate contributions of surrogates and treatment-limiting directives seemed to be mutually reinforcing in most situations (32). At the same time, the presence of a surrogate was associated with a higher likelihood of receiving care that was discordant with a treatmentlimiting directive.…”
Section: Discussionsupporting
confidence: 75%
“…In the analysis, the responders in 2015 were more willing to give a voucher than the responders in 1999. advance directives genuinely express a patient's own will. [24,25] When two short-term goals (meeting the son or a minister in the next few days) and a suspicion of iatrogenic bleeding were presented, the proportion of the physicians choosing a palliative care approach decreased, but significantly less in 2015 than in 1999. These scenarios forced the responding physicians to make ethically demanding decisions.…”
Section: Factors Associated With Physicians' Decisionsmentioning
confidence: 99%
“…Family wishes also impact medical decisions, although responsiveness to their wishes has been found to be associated with providers’ characteristics (eg, age, self-confidence regarding knowledge of medical ethics and working environment) 7 9. In a recent survey among Swiss doctors, Escher et al 6 found advance directives and relatives’ opinions to equally influence doctors’ hypothetical decision to provide treatment that could benefit a fictional patient. To our knowledge, however, no study has yet investigated which of these two sources of information is closer to what the patient would have wanted in the circumstances had he or she been able to make a decision.…”
Section: Introductionmentioning
confidence: 99%